The Permanent Collection of 1925 Oslo Modernism in Paper and Models - Lending, Mari 1969- (2014)
In 1925, architect Georg Eliassen took the initiative to establish a collection of drawings, photography and scale models in response to an increasing frustration among Norwegian architect of not being able to participate in international architectural exhibitions. The so-called Permanent Collection was founded on a principle of absolute contemporaneity, making de-acquisition as important as acquisition in the management of the collection. Nevertheless, the collection kept increasing. By the mid 1930s it included hundreds of models and innumerable drawings and photos and was seen as nucleus of an entire museum of Norwegian architecture. This ambition failed, and the material that had been so intensively displayed in Kiel, Budapest, Helsinki, Berlin, Prague, and Paris, before making its last appearance at the World’s Fair in New York in 1939, was buried in storage, dispersed, or destroyed. Based on extensive archival research, this article chronicles a forgotten collection, framing it within a modernist culture of collecting and exhibiting architecture. In November and December 2013, Mari Lending and Mari Hvattum salvaged parts of the Permanent Collection in the exhibition "Model as Ruin" at Kunstnernes Hus (House of Artists) in Oslo, the venue that hosted the most important display of the collection in 1931.
Keywords: models, exhibitions, collections, photography, publication culture